Application of Synthetic Acyl Glucopyranosides for White-rot and Brown-rot Fungal Decay Resistance in Aspen and Pine Wood - Priyanka, Matin; Md. Rezaur, Rahman; Durul, Huda; Muhammad Khusairy, Bakri; Jamal, Uddin; Yuiry, Yurkin; Andrey, Burko; Kuok King, Kuok; Mohammed Mahbubul, Matin (BioResources, 2022)
Due to its non-toxicity and environmentally friendly nature, carbohydrate-based fatty acid (CFA) esters are encouragingly used as antimicrobials and synthetic intermediates. They also are notably applied in food, surfactant, and pharmaceutical industries. In this respect, methyl 2,6-di-O-isopentanoyl-α-D-glucopyranoside (2), synthesized in a single step from methyl α-D-glucopyranoside (1), was converted into four other 3,4-di-O-acyl esters (3 - 6). All the newly synthesized CFA esters (2 - 6) were applied for the first time to study decay resistances of aspen (Populus tremula) and pine (Pinus sibirica) wood from decay caused by white-rot (Polyporous versicolor L.ex. Fr.) and brown-rot (Postia placenta (Fr). Cke.) fungi. Most of these CFA esters protected these woods from fungal attack, reduced deterioration, and preserved the weight percentage of woods at a certain point. It is noted that the CFA esters compounds reduced the deterioration and suppressed the weight percentage loss of wood at a certain point and from low to moderate decay resistances against the selected fungi.